Ionizing Radiation Impairs the Formation of Trace Fear Memories and Reduces Hippocampal Neurogenesis. - Achanta, Pragathi; Fuss, Martin; Martinez, Joe L. (Behavioral Neuroscience, 2009)
Long-term cognitive impairments are a feared consequence of therapeutic cranial irradiation in children as well as adults. Studies in animal models suggest that these deficits may be associated with a decrease in hippocampal granule cell proliferation and survival. In the present study the authors examined whether whole brain irradiation would affect trace fear conditioning, a hippocampal-dependent task. Preadolescent (postnatal Day 21, PD 21), adolescent (PD 50), and postadolescent (PD 70) rats received single doses of 0 Gray (Gy), 0.3 Gy, 3 Gy, or 10 Gy whole brain irradiation. Three months after radiation treatment, a significant dose-dependent decrease in bromo-deoxyuridine positive cells was observed. Irradiation produced a dose-dependent decrease in freezing in response to the conditioned stimulus in all age groups. Interestingly, the authors found no differences in context freezing between irradiated and control groups. Further, there were no differences in delay fear memories, which are independent of hippocampus function. Our results strongly indicate that irradiation impairs associative memories dependent on hippocampus and this deficit is accompanied by a decrease in granule cell neurogenesis indicating that these cells may be involved in normal hippocampal memory function. Reprinted by permission of the publisher.